2016
DOI: 10.1080/15592324.2016.1238545
|View full text |Cite
|
Sign up to set email alerts
|

FAR-RED ELONGATED HYPOCOTYL3 promotes floral meristem determinacy in Arabidopsis

Abstract: The transposase-derived transcription factor genes FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and FAR-RED IMPAIRED RESPONSE1 (FAR1) have redundant and multifaceted roles in plant growth and development during the vegetative stage, including phytochrome A-mediated far-red light (FR) signaling and circadian clock entrainment. Little is known about their functions in the reproductive stage. We recently demonstrated that FHY3 plays important roles in shoot apical meristem (SAM) maintenance and floral meristem (FM) determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Moreover, transcripts with roles in light signal transduction were also primarily upregulated in the mnd1.a mutant and included, for example, two FAR-RED IM-PAIRED1 (FAR1) genes (HORVU0Hr1G038960.25 and HORVU4Hr1G014170.1; Fig. 6E), which have multiple roles in plant development, including meristem as well as floral development (Wang and Wang, 2015;Liu et al, 2016). Interestingly, transcripts of Lys-specific demethylase 5D (HORVU2Hr1G045000.1) were detected only in Bowman, and not in apices of the mnd1.a mutant (Fig.…”
Section: Transcriptional Profiling By Rna Sequencingmentioning
confidence: 99%
“…Moreover, transcripts with roles in light signal transduction were also primarily upregulated in the mnd1.a mutant and included, for example, two FAR-RED IM-PAIRED1 (FAR1) genes (HORVU0Hr1G038960.25 and HORVU4Hr1G014170.1; Fig. 6E), which have multiple roles in plant development, including meristem as well as floral development (Wang and Wang, 2015;Liu et al, 2016). Interestingly, transcripts of Lys-specific demethylase 5D (HORVU2Hr1G045000.1) were detected only in Bowman, and not in apices of the mnd1.a mutant (Fig.…”
Section: Transcriptional Profiling By Rna Sequencingmentioning
confidence: 99%
“…Nevertheless, we previously isolated and functionally characterized several FM determinacy regulators via EMS mutagenesis of ag-10 (Cao et al, 2015;Li et al, 2016a). We therefore reasoned that the FM homeostasis that is perturbed in ag-10 is critical for FM maintenance and termination (Liu et al, 2016). Analysis of longitudinal sections revealed that the siliques of cytokinin-treated ag-10 had more bulges compared with untreated plants and produced additional tissues within the primary carpel, indicating a severe FM determinacy defect due to exogenous cytokinin treatment (Figures 1C and 1D).…”
Section: Exogenous Cytokinin Treatment Enhances the Fm Determinacy Dementioning
confidence: 99%
“…Besides regulating WUS expression directly and indirectly (Sun et al, 2009;Liu et al, 2011), AG helps maintain FM homeostasis. In terms of genome-wide gene expression, the impact of the ag-10 point mutation is minimal, but FM homeostasis is effectively destroyed: in the ag-10 genetic background, even small perturbations in the FM determinacy regulatory network are amplified and result in severe FM determinacy defects (Liu et al, 2016). For example, the expression of major cytokinin biosynthesis and signaling genes, such as IPTs, AHK4, ARRs, and LOGs, was significantly derepressed in ag-10 arf3-29 relative to the single ag-10 and arf3-29 mutants (Figures 2F and 4B), indicating that ARF3 and AG function synergistically to regulate cytokinin activity.…”
Section: Arf3 Acts Synergistically With Ag In Fm Maintenance and Detementioning
confidence: 99%
“…The Arabidopsis FHY3 protein directly activates the E‐class MADS‐box gene SEPALLATA2 ( SEP2 ) (Liu et al ., 2016). We have demonstrated that the tap mutation causes the downregulation of 10 OsMADS genes and three YAB genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One such protein family is the FAR‐RED IMPAIRED RESPONSE1 (FAR1)‐related sequences (FRS) family of transcription factors in Arabidopsis (Hudson et al ., 2003). Arabidopsis FAR1 and FAR‐RED ELONGATED HYPOCOTYLS3 (FHY3) are homologous FRS proteins that participate in a wide range of cellular processes, including signal transduction in photomorphogenesis (Hudson et al ., 1999, 2003), circadian clock regulation (Allen et al ., 2006; Li et al ., 2011), chloroplast division (Chang et al ., 2015), abscisic acid signaling (Tang et al ., 2013), and shoot meristem and floral development (Stirnberg et al ., 2012; Li et al ., 2016; Liu et al ., 2016). Despite the higher number of FRS genes in monocot genomes, their functions are poorly understood.…”
Section: Introductionmentioning
confidence: 99%